Ash [videorecording (DVD)] - Flying Lotus, 1983-; Flying Lotus, 1983-; Remmler, Jonni, 1991-; González, Eiza, 1990-; Paul, Aaron, 1979-; Uwais, Iko, 1983-; Elliott, Kate, 1981-; Koale, Beulah, 1992-; Bluck, Richard; Throup, Aitor (Shudder, 2025)
"On the mysterious planet of ASH, Riya awakens to find her crew slaughtered. When a man named Brion arrives to rescue her, and ordeal of psychological and physical terror ensues, while Riya and Brion must decide if they can trust one another to survive."--